Integriertes optisches Spektrometer - Scheytt, J. Christoph; Schwabe, Tobias

Optoelektronischer Oszillator - Kruse, Stephan; Scheytt, J. Christoph

Simulation and Optimization of Low-Loss Photonic Coupling Structures for TFLN Integrated Circuits for Quantum Applications - Mihaylov, Martin Miroslavov; Kress, Christian; Scheytt, J. Christoph

Mehrband-Sensorsystem zur Umfelderfassung, sowie Verfahren und Kraftfahrzeug - Kruse, Stephan; Scheytt, J. Christoph; Schwabe, Tobias; Heiko Gustav, Kurz; Marc-Michael, Meinecke

Quantenoptisch-unterstütztes Sende-/Empfangssystem - Kruse, Stephan; Brecht, Benjamin; Silberhorn, Christine; Serino, Laura Maria

Analysis and Simulation of a Photonic Multiband FMCW Radar Sensor System using Nyquist Pulses - Kruse, Stephan; Schwabe, Tobias; Kneuper, Pascal; Kurz, Heiko G.; Meinecke, March-Michael; Scheytt, Christoph (German Microwave Conference (GeMiC))

A Photonic Multiband Radar Transmitter Architecture with Tailored Nonlinear Transmission Line - Kruse, Stephan; Schwabe, Tobias; Kneuper, Pascal; Scheytt, J. Christoph (INTERNATIONAL CONFERENCE RADAR 2024)

Phase Noise Analysis of Photonic Radar Systems with Optical LO Distribution - Kruse, Stephan; Kneuper, Pascal; Schwabe, Tobias; Kurz, Heiko G.; Meinecke, Marc-Michael; Gonzalez-Huici, María A.; Scheytt, J. Christoph (International Conference on Microwaves for Intelligent Mobility (ICMIM))

Doppler Analysis of a Lidar-Photonic Radar Combined Sensor System - Kruse, Stephan; Brockmeier, Jan; Kneuper, Pascal; Schwabe, Tobias; Kurz, Heiko G.; Meinecke, Marc Michael; Scheytt, J. Christoph (International Radar Symposium (IRS))

A Quantum Pulse Gate Enhanced Photonic Radar Architecture - Kruse, Stephan; Brecht, Benjamin; Silberhorn, Christine

Photonically Assisted Sampling Circuits - Weizel, Maxim; Scheytt, J. Christoph

Implementation of Different Communication Structures for a Rocket Chip Based RISC-V Grid of Processing Cells - Luchterhandt, Lars; Nellius, Tom; Beck, Robert; Dömer, Rainer; Kneuper, Pascal; Müller, Wolfgang; Sadiye, Babak (MBMV 2024 - 27. Workshop Methoden und Beschreibungssprachen zur Modellierung und Verifikation von Schaltungen und Systemen“)
RISC-V has received worldwide acceptance in the industry and by the academic community. As of today, multiple RISC-V applications and variants are under investigation for embedded IoT systems, from resource-limited single-core processors up to multi-core systems for High-Performance Computing (HPC). Recently, the Grid of Processing Cells (GPC) platform has been proposed as a scalable parallel grid-oriented network of processor cores with local memories. This paper describes a prototype design of the GPC platform for hardware implementation at Register-Transfer Level (RTL) based on modified RISC-V Rocket processors with scratchpad memories. It introduces a scalable Chisel-based implementation of the modified Rocket cores with RTL generation and a functional test using Verilator simulation. This work also includes the adaptation of the Chipyard software toolchain to extend the compiler to multi-core grids with different local address spaces.

Scale4Edge – Scaling RISC-V for Edge Applications - Ecker, Wolfgang; Krstic, Milos; Ulbricht, Markus; Mauderer, Andreas; Jentzsch, Eyck; Koch, Andreas; Koppelmann, Bastian; Müller, Wolfgang; Sadiye, Babak; Bruns, Niklas; Drechsler, Rolf; Müller-Gritschneder, Daniel; et al. (RISC-V Summit Europe 2023, Barcelona, Spain, June 2023.)

Der TETRISC SoC - Ein resilientes Quad-Core System auf Pulpissimo-Basis - Müller, Wolfgang; Ulbricht, Markus; Li, Lu; Krstic, Milos (5. ITG / GMM / GI -Workshop Testmethoden und Zuverlässigkeit von Schaltungen und Systemen)

A 28-Gb/s 27.2mW NRZ Full-Rate Bang-Bang Clock and Data Recovery in 22 nm FD-SOI CMOS Technology - Iftekhar, Mohammed; Gowda, Harshan; Kneuper, Pascal; Sadiye, Babak; Müller, Wolfgang; Scheytt, Christoph (2023 IEEE BiCMOS and Compound Semiconductor Integrated Circuits and Technology Symposium (BCICTS))

Optimized, Highly Efficient Silicon Antennas for Optical Phased Arrays - Farheen, Henna; Strauch, Andreas; Scheytt, J. Christoph; Myroshnychenko, Viktor; Förstner, Jens (Photonics and Nanostructures - Fundamentals and Applications)
Silicon photonics, in conjunction with complementary metal-oxide-semiconductor (CMOS) fabrication, has greatly enhanced the development of integrated optical phased arrays. This facilitates a dynamic control of light in a compact form factor that enables the synthesis of arbitrary complex wavefronts in the infrared spectrum. We numerically demonstrate a large-scale two-dimensional silicon-based optical phased array (OPA) composed of nanoantennas with circular gratings that are balanced in power and aligned in phase, required for producing elegant radiation patterns in the far-field. For a wavelength of 1.55 μm, we optimize two antennas for the OPA exhibiting an upward radiation efficiency as high as 90%, with almost 6.8% of optical power concentrated in the field of view. Additionally, we believe that the proposed OPAs can be easily fabricated and would have the ability to generate complex holographic images, rendering them an attractive candidate for a wide range of applications like LiDAR sensors, optical trapping, optogenetic stimulation, and augmented-reality displays.
Keywords: tet_topic_opticalantenna

A Pulsed Lidar System With Ultimate Quantum Range Accuracy - Kruse, Stephan; Serino, Laura; Folge, Patrick Fabian; Echeverria Oviedo, Dana; Bhattacharjee, Abhinandan; Stefszky, Michael; Scheytt, J. Christoph; Brecht, Benjamin; Silberhorn, Christine (IEEE Photonics Technology Letters)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Generation of 100 GHz Periodic Nyquist Pulses using Cascaded Mach-Zehnder Modulators in a Silicon Electronic-Photonic Platform - Kress, Christian; Schwabe, Tobias; Silberhorn, Christine; Scheytt, J. Christoph (Conference on Lasers and Electro-Optics (CLEO) 2023)
A frequency-flexible Nyquist pulse synthesizer is presented with optical pulse bandwidths up to fopt=100 GHz and repetition rates equal to fopt/9, fabricated in an electronic-photonic co-integrated platform utilizing linear on-chip drivers.

Verfahren zum Betreiben einer elektrooptischen Übertragungsvorrichtung für beliebige Signale, Computerprogrammprodukt sowie Datenübertragungsvorrichtung - Kruse, Stephan; Scheytt, J. Christoph; Meinecke, Marc-Michael; Heiko Gustav, Kurz
Die Erfindung betrifft ein Verfahren zum Betreiben einer elektrooptischen Übertragungsvorrichtung, mit den Schritten: - Erzeugen eines optischen Trägersignals mittels einer optischen Signalquelle einer Basiseinrichtung der Übertragungsvorrichtung; - Erzeugen eines beliebigen Signals mittels der optischen Signalquelle; - Aufmodulieren des beliebigen Signals auf das optische Trägersignal in der Basiseinrichtung zu einem Übertragungssignal; - Übertragen des Übertragungssignals an eine Antenneneinrichtung der Übertragungsvorrichtung mittels eines optischen Übertragungsmediums; und - Trennen des beliebiges Signals und des Trägersignals in der Antenneneinrichtung. Ferner betrifft die Erfindung ein Computerprogrammprodukt sowie eine Übertragungsvorrichtung.

Elektrooptischer Balun und System zur Generierung eines pseudodifferentiellen Signals aufweisend einen solchen elektrooptischen Balun - Kruse, Stephan; Scheytt, J. Christoph
Die Erfindung betrifft einen elektrooptischen Balun, wobei der elektrooptische Balun einen Eingang für ein optisches Eingangssignal (Ein(t)) aufweist, wobei der elektrooptische Balun weiterhin ein 1x2 Multimodeninterferometer (1x2 MMI) und einen Phasenschieber (Δϕ) aufweist, wobei das 1x2 Multimodeninterferometer (1x2 MMI) mit dem Eingangssignal im Betrieb versorgbar ist, wobei der elektrooptische Balun weiterhin ein 2x4 Multimodeninterferometer (2x4 MMI) aufweist, wobei das 2x4 Multimodeninterferometer (2x4 MMI) mit den Ausgangsarmen des 1x2 Multimodeninterferometer (1x2 MMI) verbunden ist, wobei der Phasenschieber (Δϕ) in einem Ausgangsarm des 1x2 Multimodeninterferometer (1x2 MMI) angeordnet ist, wobei im Betrieb an zwei Ausgängen (Eout,1 (t), Eout,4(t)) des 2x4 Multimodeninterferometers (2x4 MMI) ein quasi differentielles optisches Signal anliegt, das mittels einer jeweiligen Photodiode (PD1, PD2) und einem differentiellen Schaltkreis in ein DC-freies elektrisches Signal (Vout) überführt werden kann. Weiterhin betrifft die Erfindung ein System zur Generierung eines pseudeodifferentiellen Signals, aufweisend einen elektrooptischen Balun sowie einen optischen Strahlteiler (OS) sowie einen dual output carrier injection Mach Zehnder Modulator (MZM), wobei der optische Strahlteiler (OS) ein Eingangssignal (IIN) in einen ersten Teil (n) und einen zweiten Teil (1-n) aufteilt, wobei der zweite Teil (1-n) als Eingangssignal (Ein(t)) im Betrieb auf den Eingang des elektrooptischen Baluns geführt wird, wobei der erste Teil (n) im Betrieb als Eingangssignal dem dual output carrier injection Mach Zehnder Modulator (MZM) zugeführt wird, wobei das quasi differentielle elektrische Signal (I1, I2) der Photodioden (PD1, PD2) im Betrieb zur Ansteuerung des dual output carrier injection Mach Zehnder Modulator (MZM) in push pull Konfiguration verwendet wird.